Ceramic particle surface treatment method and metal-based ceramic composite material
By ball milling and cleaning the ceramic particles, and using cold spray technology to deposit nanoscale active material powder, the problem of poor wettability between the ceramic particles and the metal liquid is solved, and a more efficient composite process and lower cost are achieved.
Patent Information
- Application Number
- CN202410906804.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-08
- Publication Date
- 2025-01-21
AI Technical Summary
During the composite process, existing metal-based ceramic composite materials have problems such as poor wettability between ceramic particles and metal liquid, complex process and high cost.
A ceramic particle surface treatment method is adopted, including ball milling and cleaning the ceramic particles to remove impurities and increase surface roughness, and then use cold spray technology to evenly deposit nanoscale active material powder on the surface of the preheated ceramic particles.
The bonding ability between metal liquid and ceramic particles is improved, impregnation defects are avoided, production costs are reduced, and the process flow is simplified.
Smart Images

Figure CN119332236A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal-based ceramic composite materials, and more specifically to a ceramic particle surface treatment method and a metal-based ceramic composite material. Background Art
[0002] In the metallurgy, cement, mining, power and other industries, there is a huge demand for wear-resistant parts, and metal-based ceramic composites are ideal substitutes for traditional wear-resistant materials due to their excellent wear resistance and toughness. However, in order to obtain a well-compounded metal-based ceramic composite, while taking into account factors such as production costs, it is necessary to solve the problems of wettability between ceramic particles and metal matrix and wetting defects caused by differences in thermal expansion coefficients.
[0003] At present, the reinforcement particles of the widely used metal-ceramic composite wear-resistant products are mostly low-cost ZTA ceramic particles. However, due to the poor wettability of ZTA ceramic particles with molten metal, it is necessary to improve the infiltration effect of ZTA ceramic particles with molten metal by coating the surface of ZTA ceramic particles with active element powder.
[0004] Chinese invention patent CN111283176A discloses a method for preparing an extrusion roller, in which ceramic particles and metal powder are fully mixed, a binder is added, and then the mixture is added to a post nail preform forming mold to obtain a post nail ceramic preform, and then the preform is fixed to a die-casting mold to cast a high-temperature molten metal. In this method, the ceramic particles and the metal powder are bonded by a binder, and the metal powder is unevenly coated, which easily produces infiltration defects during the casting process; Chinese invention patent CN116441515A discloses a composite preparation method for metal-based ceramic composite materials, in which ceramic particles, a binder, and a mixed powder are evenly mixed, filled into a mold and cured to obtain a ceramic preform, and then the ceramic preform is heated and poured with molten metal to obtain a metal-based ceramic composite material. In this method, the ceramic particles and the metal powder are also bonded by a binder, and the metal powder is unevenly coated; Chinese invention patent CN112207273A discloses A wear-resistant, long-life metal-based ceramic composite material and a preparation method thereof are disclosed. In this method, a Ni-P alloy layer is plated on the surface of ZTA ceramic particles by chemical plating or electroplating, and then mixed with a pore-forming agent, a binder and powders such as SiC, Ti, and FeB (ferrous boride). After vacuum sintering, a ceramic preform is obtained, and then a molten metal is poured. This method combines chemical plating or electroplating with a binder to achieve the purpose of good infiltration of ceramic particles and molten metal, and the process is relatively complicated; Chinese invention patent CN103143699A discloses a metal-ceramic preform composite reinforced wear-resistant part and a preparation method thereof. In this method, ceramic particles are first prepared into a ceramic preform, and then a layer of nickel-based self-fluxing alloy powder is sprayed on the surface of the ceramic preform by thermal spraying or plasma spraying, and then the molten metal is poured to obtain a metal-ceramic composite reinforced wear-resistant part. However, this method requires heating the coated particles to a molten or semi-molten state, and the production cost is relatively high.
[0005] In summary, at present, in the composite process of metal-based ceramic composite materials, the preparation of ceramic preforms is mainly to achieve micro-powder coating of ceramic particles through a binder, or to plate a layer of nickel or chromium on the surface of ceramic particles by chemical plating or electroplating, or to spray metal powder on the surface of ceramic particles by thermal spraying, so as to improve the infiltration effect between ceramic particles and metal matrix. However, when active element powder is directly mixed and bonded with ceramic particles by a binder, there is a problem of uneven coating of active elements and ceramic particles; by chemical plating or electroplating, the types of metal powders that can be plated are very limited, which is not suitable for large-scale application and promotion; by thermal spraying, metal powder is sprayed on the surface of ceramic particles, and a semi-metallurgical bond can be formed between the powder and the ceramic particles, which has a good effect, but the metal powder needs to be heated to a molten or semi-melted state, which is costly. Summary of the invention
[0006] The invention provides a ceramic particle surface treatment method and a metal-based ceramic composite material, which are used to solve the problems of uneven coating of active substances, complex process and high cost of the metal-based ceramic composite material in the prior art.
[0007] The present invention provides a method for treating the surface of ceramic particles, comprising:
[0008] S1, ball milling and cleaning the ceramic particles, removing impurities on the surface of the ceramic particles and increasing the surface roughness of the ceramic particles;
[0009] S2. After preheating the pretreated ceramic particles, nanometer-scale active material powder is evenly deposited on the surface of the preheated ceramic particles by cold spraying to obtain treated ceramic particles.
[0010] Optionally, the S1 includes:
[0011] S11, ball milling the ceramic particles, and immersing the ball-milled ceramic particles in an acetone solution and cleaning them with ultrasonic vibration;
[0012] S12, pickling the cleaned ceramic particles.
[0013] Optionally, in S2, the preheating temperature is 300-700°C;
[0014] During cold spraying, the gas pressure is controlled to be 1.5-5MPa and the inlet temperature of the accelerating gas is 100-800°C.
[0015] Optionally, in S2, the steps for preparing nano-scale active material powder are as follows:
[0016] S21, mixing different types of active substance powders according to proportion to obtain a first mixture;
[0017] S22, adding the first mixture and the dispersant into a ball mill for ball milling, and sieving the second mixture of the first particle size from the ball-milled powder;
[0018] S23, adding the second mixture and the dispersant into a ball mill and milling again to obtain a third mixture; and sieving out nano-scale active material powder of a second particle size from the third mixture.
[0019] Optionally, in S21, the types of active materials include at least two of Al2O3 powder, B4C powder, SiC powder, Fe-based self-fluxing alloy powder and Ni-based self-fluxing alloy powder;
[0020] The particle sizes of the Al2O3 powder, B4C powder and SiC powder are 500-700 meshes, and the particle sizes of the Fe-based self-fluxing alloy powder and the Ni-based self-fluxing alloy powder are 800-1000 meshes.
[0021] Optionally,
[0022] When the active substance includes two powders, the mixing ratio of the two powders is 1:1 to 1:2;
[0023] When the active substance includes three powders, the mixing ratio of the three powders is 1:1:1 to 1:1:3;
[0024] When the active material includes four or more powders, the four or more powders are mixed in equal proportions.
[0025] Optionally, in S22, the diameter of the first grinding balls used in the ball mill is 4-6 mm, the first rotation speed of the ball mill is 100-150 r / min; the first ball-to-material ratio is 3:1-6:1; and the first particle size is less than 100 nm.
[0026] Optionally, in S23, the diameter range of the second grinding balls used in the ball mill is 3 to 5 mm, the first speed range of the ball mill is 150 to 220 r / min; the first ball-to-material ratio is 4:1 to 10:1; the second particle size is less than 50 nm; and the ball milling time range is 24 to 48 h.
[0027] Optionally,
[0028] The first grinding ball is any one of a silicon carbide ball, a zirconium oxide ball and a cemented carbide ball.
[0029] Optionally,
[0030] The second grinding ball is any one of a silicon carbide ball, a zirconium oxide ball and a cemented carbide ball.
[0031] Optionally, the dispersant is ammonium polyacrylate and / or sodium dodecyl sulfate.
[0032] Optionally, the ceramic particles in S1 are one or more of zirconium corundum ceramic particles, aluminum oxide ceramic particles, silicon nitride ceramic particles, titanium nitride ceramic particles, silicon carbide ceramic particles or titanium carbide ceramic particles.
[0033] The present invention also provides a method for preparing a metal-based ceramic composite material, comprising:
[0034] S1. Treating the surface of ceramic particles by the ceramic particle surface treatment method of the present invention to obtain first ceramic particles;
[0035] S2: Using the first ceramic particles to prepare a metal-based ceramic composite material
[0036] S21, uniformly atomizing a mixture of a sodium silicate aqueous solution and water on the surface of the first ceramic particles to obtain second ceramic particles;
[0037] S22, filling the second ceramic particles into a honeycomb mold, and obtaining a honeycomb ceramic preform after curing;
[0038] S23, drying the ceramic preform, placing the dried ceramic preform in a mold cavity, injecting molten metal into the mold cavity and then solidifying the molten metal to obtain a metal-based ceramic composite material.
[0039] Optionally, in S21, the mixing weight ratio of the sodium silicate aqueous solution to water is 4:1 to 9:1;
[0040] The atomization control atomization spray pressure is 0.2-0.8 MPa, the atomization flow rate is 2-10 g / s, and the atomization spray amount of the mixture of the sodium silicate aqueous solution and water accounts for 4%-8% of the total weight of the first ceramic particles;
[0041] During the atomization process, the first ceramic particles are vibrated.
[0042] Optionally, the S22 includes:
[0043] S221, filling the second ceramic particles into a honeycomb mold;
[0044] S222, continuously introducing CO2 gas into the honeycomb mold for 1 to 2 minutes;
[0045] S223, keeping the honeycomb mold at a temperature of 50 to 100° C. for 18 to 24 hours to solidify the second ceramic particles in the mold to obtain a honeycomb ceramic preform.
[0046] Optionally, in S23, the drying temperature of the ceramic preform is 150-200° C., and the drying time is 20-40 min.
[0047] Optionally, in S23, the molten metal is high-chromium cast iron liquid or high-alloy steel liquid; the temperature of the injected molten metal is controlled to be 1500-1580°C.
[0048] Optionally, the metal-based ceramic composite material is prepared by the preparation method of the present invention.
[0049] The present invention has at least the following beneficial effects:
[0050] 1. By processing the active material powder into a uniform nano-level and utilizing the strong adsorption function of the nano-powder, the active material powder can be more firmly combined with the ceramic particles during the cold spraying process, thereby improving the bonding ability between the metal liquid and the ceramic particles.
[0051] 2. The present invention uses cold spraying to uniformly deposit nanometer-scale active material powder on the surface of ceramic particles to achieve activation of the ceramic particles, namely "metallization", thereby improving the wettability of ceramics and metals. The nanometer-scale active material powder has a high bonding strength with the ceramic particles, which is beneficial to the infiltration of the metal liquid and the ceramic particles during the composite process, avoiding infiltration defects caused by loose powder bonding during the casting process, and having a higher yield rate.
[0052] 3. The cold spraying method has a lower working temperature, which can maintain the original characteristics of the spraying powder to the greatest extent, making the operation simpler. At the same time, the cold spraying process will not produce harmful substances such as wastewater and exhaust gas, making the operation safer and more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0054] Figure 1 A composite morphology diagram of a metal-ceramic composite material provided by an embodiment of the present invention;
[0055] Figure 2 This is a microstructure diagram of the composite area of the metal-ceramic composite material provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0056] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] The present invention provides a method for treating the surface of ceramic particles, comprising:
[0058] S1, ball milling and cleaning the ceramic particles, removing impurities on the surface of the ceramic particles and increasing the surface roughness of the ceramic particles;
[0059] S2. After preheating the pretreated ceramic particles, nanometer-scale active material powder is evenly deposited on the surface of the preheated ceramic particles by cold spraying to obtain treated ceramic particles.
[0060] Specifically, S1, pre-treating the ceramic particles, the pre-treating includes ball milling the ceramic particles, cleaning them after ball milling, and then removing impurities on the surface of the particles, while removing the surface impurities, the surface roughness of the ceramic particles can be increased. Increasing the surface roughness of the ceramic particles is conducive to better adhesion of the nano-scale active material powder mixture to the surface of the ceramic particles during the cold spraying process, forming a tighter bond.
[0061] S2, preheating the pretreated ceramic particles, and uniformly depositing the nano-scale active substance powder on the surface of the preheated ceramic particles by cold spraying. Preheating the ceramic particles can increase the surface temperature of the ceramic particles, increase the adhesion and permeability of the nano-scale active substance powder mixture during the spraying process. This enhanced adhesion and permeability helps to form a tighter and stronger coating, which can improve the bonding strength between the coating and the substrate. Nano-scale active substance powder refers to a material powder that has good wettability with the metal liquid.
[0062] Regarding the cold spraying technology, the characteristic of the cold spraying technology is to achieve the deposition of the coating material on the surface of the material to be sprayed at a lower temperature. The powder particles are sprayed onto the surface of the material to be sprayed in the sample chamber by a nozzle in a high-speed impact manner to form a coating on the surface of the material to be sprayed. Among them, the nano-scale active material powder is loaded into the powder feeder of the cold spraying equipment, and the gas source is connected. The gas enters the nozzle after being heated by the gas spiral heater, and merges with the active material powder at the nozzle. The active material powder is accelerated by the gas in the nozzle, sprayed out through the nozzle of the spraying equipment, and hits the ceramic particles in the spraying chamber to complete the deposition of the powder on the ceramic particles. The gas source can be compressed air or an inert gas or a mixed gas of compressed air and an inert gas. The inert gas can be nitrogen, argon and helium. The nozzle in the cold spraying device is a Laval nozzle. The Laval nozzle has the characteristics of fast spray speed, high precision and stable operation. The nozzle diameter ranges from 1 to 3 mm, preferably 2 mm, and the ratio of the outlet diameter to the inlet diameter is between 1:5 and 1:3.
[0063] Since the nano-scale active material powder particles do not melt during the entire spraying process, this technology is called "cold spraying". Through cold spraying technology and setting reasonable cold spraying parameters, the nano-scale active material powder mixture can be deposited on the surface of the preheated ceramic particles in a uniform manner, avoiding the coating being too thick or too thin, and obtaining ceramic particles with nano-scale active material powder uniformly coated on the surface. By utilizing the self-adsorption of nanoparticles, the active element powder is uniformly deposited on the surface of the ceramic particles, realizing the activation of the ceramic particle surface.
[0064] In a possible implementation manner, the S1 includes:
[0065] S11, ball milling the ceramic particles, and immersing the ball-milled ceramic particles in an acetone solution and cleaning them with ultrasonic vibration;
[0066] S12, pickling the cleaned ceramic particles.
[0067] Specifically, S11, ball milling the ceramics with a ball mill, with the control parameters being: a rotation speed of 50 to 100 r / min, and a ball milling time of 1.5 to 3 hours. After ball milling, the ceramics are soaked in acetone and ultrasonically cleaned to remove oil or dust.
[0068] S12, pickling the cleaned ceramic particles to corrode impurities on the surface of the ceramic particles and increase the surface roughness. Different degrees of surface roughening can be achieved by selecting appropriate acid type, concentration and treatment time.
[0069] In a possible implementation manner, in S2, the preheating temperature is 300-700° C.;
[0070] During cold spraying, the gas pressure is controlled to be 1.5-5MPa and the inlet temperature of the accelerating gas is 100-800°C.
[0071] Specifically, the surface temperature of the preheated ceramic particles is relatively high, which helps the nano-scale active material powder to better embed into the surface of the ceramic particles when impacting, forming a tighter coating and improving the bonding strength of the coating.
[0072] In addition, when the nano-scale active material powder is deposited on the preheated ceramic surface by cold spraying, the reasonable setting of cold spraying parameters can improve the spraying effect. Among them, the spraying gas pressure range is 1.5-5MPa, and the appropriate gas pressure can ensure that the nano-scale active material powder obtains sufficient kinetic energy to embed into the surface of the ceramic particles. In addition, the inlet temperature of the accelerating gas ranges from 100 to 800°C, which can further soften the nano-scale active material powder and improve the bonding strength of the coating. Too high a temperature may cause the particles to melt, affecting the structure and performance of the coating. A suitable powder delivery flow rate can ensure that the coating has a uniform thickness. The reasonable setting of the distance from the nozzle outlet to the sample spraying chamber can enable the nano-scale active material powder particles to maintain an appropriate speed and temperature when they reach the surface of the ceramic particles, ensuring the quality and uniformity of the coating. During cold spraying, the powder delivery flow rate is 10-50g / min, and the thickness of the nano-scale active material powder on the surface of the treated ceramic particles is 20-90μm.
[0073] In a possible implementation, in S2, the steps of preparing the nanoscale active substance powder are as follows:
[0074] S21, mixing different types of active substance powders according to proportion to obtain a first mixture;
[0075] S22, adding the first mixture and the dispersant into a ball mill for ball milling, and sieving the second mixture of the first particle size from the ball-milled powder;
[0076] S23, adding the second mixture and the dispersant into a ball mill and milling again to obtain a third mixture; and sieving out nano-scale active material powder of a second particle size from the third mixture.
[0077] Specifically, the active material powder is ground to a particle size of nanometer level, which significantly increases the specific surface area and surface activity of the active material and facilitates the combination with subsequent ceramic particles.
[0078] Through the two ball milling processes, the particle size of the active material powder can be further reduced. At the same time, the active material powder to be ball milled is ground together with the dispersant. The addition of the dispersant helps the active material powder to be better dispersed during the ball milling process and prevent the occurrence of agglomeration.
[0079] In a possible implementation, the types of active materials include at least two of Al2O3 powder, B4C powder, SiC powder, Fe-based self-fluxing alloy powder and Ni-based self-fluxing alloy powder;
[0080] The particle sizes of the Al2O3 powder, B4C powder and SiC powder are 500-700 meshes, and the particle sizes of the Fe-based self-fluxing alloy powder and the Ni-based self-fluxing alloy powder are 800-1000 meshes.
[0081] In a possible implementation, when the active substance includes two powders, the mixing ratio of the two powders is 1:1 to 1:2;
[0082] When the active substance includes three powders, the mixing ratio of the three powders is 1:1:1 to 1:1:3;
[0083] When the active material includes four or more powders, the four or more powders are mixed in equal proportions.
[0084] During the preparation process, maintaining a stable mixing ratio of active substance powder can improve the stability and repeatability of the process and reduce fluctuations and uncertainties in the production process.
[0085] In a possible implementation, in S22, the diameter of the first grinding balls used in the ball mill is 4-6 mm, the first rotation speed of the ball mill is 100-150 r / min, the first ball-to-material ratio is 3:1-6:1, and the first particle size is less than 100 nm.
[0086] In a possible implementation, in S23, the diameter range of the second grinding balls used in the ball mill is 3 to 5 mm, the first speed range of the ball mill is 150 to 220 r / min; the first ball-to-material ratio is 4:1 to 10:1; the second particle size is less than 50 nm; and the ball milling time range is 24 to 48 h.
[0087] From step 22 to step 23, the rotation speed of the ball mill is increased from 100-150 r / min to 150-220 r / min, and the ball-to-material ratio is increased from 3:1-6:1 to 4:1-10:1, which increases the collision frequency and energy between the grinding balls, and further crushes the active material powder in the ball mill. In addition, in the final grinding stage to obtain nano-scale active material powder, by controlling the ball milling time, it is ensured that the active material powder can reach the required second particle size and the particle size distribution is more uniform.
[0088] Step 22 is the first stage of ball milling the active powder, and the diameter of the grinding balls ranges from 4 to 6 mm. Step 23 is the second stage of ball milling the active powder, and the diameter of the grinding balls ranges from 3 to 5 mm. The diameter of the grinding balls selected in the second stage is smaller than the diameter of the grinding balls in the first stage. The first stage performs preliminary refinement of the powder, and the second stage further refines the powder refined in the first stage to make the powder particle size more uniform.
[0089] In a possible implementation manner, the first grinding ball is any one of a silicon carbide ball, a zirconium oxide ball and a cemented carbide ball.
[0090] In a possible implementation manner, the second grinding ball is any one of a silicon carbide ball, a zirconium oxide ball and a cemented carbide ball.
[0091] In a possible implementation, the dispersant is ammonium polyacrylate and / or sodium dodecyl sulfate.
[0092] In a possible implementation, the ceramic particles in S1 are one or more of zirconium corundum ceramic particles, aluminum oxide ceramic particles, silicon nitride ceramic particles, titanium nitride ceramic particles, silicon carbide ceramic particles or titanium carbide ceramic particles. The dispersant may be ammonium polyacrylate or sodium dodecyl sulfate, or a mixture of ammonium polyacrylate and sodium dodecyl sulfate.
[0093] The present invention also provides a method for preparing a metal-based ceramic composite material, comprising:
[0094] S1. Treating the surface of ceramic particles using the treatment method of claim 1 to obtain first ceramic particles;
[0095] S2: Using the first ceramic particles to prepare a metal-based ceramic composite material
[0096] S21, uniformly atomizing a mixture of a sodium silicate aqueous solution and water on the surface of the first ceramic particles to obtain second ceramic particles;
[0097] S22, filling the second ceramic particles into a honeycomb mold, and obtaining a honeycomb ceramic preform after curing;
[0098] S23, drying the ceramic preform, placing the dried ceramic preform in a mold cavity, injecting molten metal into the mold cavity and then solidifying the molten metal to obtain a metal-based ceramic composite material.
[0099] Specifically, S1, the ceramic particles are cleaned after ball milling, and then surface impurities are removed and surface roughness is increased to complete the pretreatment of the ceramic particles. Then, nano-scale active material powder is evenly deposited on the surface of the pretreated ceramic particles by cold spraying to obtain first ceramic particles.
[0100] S21, uniformly atomize the mixture of sodium silicate aqueous solution and water on the surface of the first ceramic particles to obtain second ceramic particles. The mixture of sodium silicate aqueous solution and water has higher high temperature resistance and excellent chemical stability as a binder. The mixture of sodium silicate aqueous solution and water is sprayed onto the surface of the second ceramic particles by atomization, so that the mixture of sodium silicate aqueous solution and water can be evenly covered on the surface of the ceramic particles, and the spraying amount is easy to control.
[0101] S22, filling the second ceramic particles into a honeycomb mold, and obtaining a ceramic preform after curing. The second ceramic particles treated with a binder are filled into a honeycomb mold and cured, so that the second ceramic particles form a stable network structure in a honeycomb three-dimensional space to obtain a honeycomb ceramic preform. Since there are certain gaps in the honeycomb ceramic preform, the subsequent molten metal can fully penetrate into these gaps during the injection process and form a close contact with the ceramic particles.
[0102] S23, drying the ceramic preform, placing the dried ceramic preform in a mold cavity, injecting molten metal into the mold cavity and solidifying it to obtain a metal-based ceramic composite material. When the molten metal comes into contact with water at high temperature, a violent chemical reaction may occur, producing gases such as hydrogen. This may cause the molten metal to splash, and may also form pores or inclusions inside the metal-based ceramic composite material, thereby reducing the performance and strength of the material. Therefore, by drying and removing the moisture in the ceramic preform, the occurrence of adverse reactions can be avoided. After the molten metal is cooled in the casting cavity, it is demolded to obtain a finished product.
[0103] Through cold spraying, the active material powder can be wrapped more evenly and firmly, which is beneficial to the infiltration of metal liquid and ceramic particles, reduces infiltration defects, and improves the yield rate. At the same time, the cost is lower and the production process is safer and more environmentally friendly. In the preparation process of ceramic preforms, the binder is combined with the ceramic particles in an atomized manner, the binder is more uniform, and the strength of the ceramic preform is higher, avoiding the collapse problem caused by insufficient strength of the preform during the casting process.
[0104] In a possible implementation, in S21, the weight ratio of the sodium silicate aqueous solution to water is 4:1 to 9:1;
[0105] The atomization control atomization spray pressure is 0.2-0.8 MPa, the atomization flow rate is 2-10 g / s, and the atomization spray amount of the mixture of the sodium silicate aqueous solution and water accounts for 4%-8% of the total weight of the first ceramic particles;
[0106] During the atomization process, the first ceramic particles are vibrated.
[0107] Specifically, suitable atomization spraying pressure and flow rate can make the mixture of sodium silicate aqueous solution and water be sprayed evenly onto the surface of the second ceramic particles, and higher atomization pressure helps to form finer droplets, increase the contact area between the droplets and the ceramic particles, thereby improving the coverage effect and uniformity of the sodium silicate. When the binder is atomized onto the surface of the second ceramic particles, the distribution shape of the droplets formed by atomization can be circular or conical.
[0108] The atomized spraying amount of the mixture of sodium silicate aqueous solution and water accounts for 4% to 8% of the total weight of the first ceramic particles, so that sodium silicate covers the surface of the ceramic particles in an appropriate amount. Too much sodium silicate may cause the coating to be too thick, affecting the performance of the ceramic particles, while too little sodium silicate may not fully play its role in improving the ceramic performance. By precisely controlling the spraying amount of sodium silicate and continuously vibrating the first ceramic particles during the atomization spraying process, the sodium silicate aqueous solution is atomized more evenly on the surface of the first ceramic particles. While ensuring the uniformity of the coating, the optimization of ceramic performance is achieved.
[0109] In a possible implementation manner, the S22 includes:
[0110] S221, filling the second ceramic particles into a honeycomb mold;
[0111] S222, continuously introducing CO2 gas into the honeycomb mold for 1 to 2 minutes;
[0112] S223, keeping the honeycomb mold at a temperature of 50 to 100° C. for 18 to 24 hours to solidify the second ceramic particles in the mold to obtain a honeycomb ceramic preform.
[0113] Specifically, during the curing process of the ceramic preform, CO2 gas can fully react with the binder to accelerate the hardening speed of the ceramic preform. Keeping the temperature at 50-100°C for 18-24 hours can make the ceramic preform cure more fully and make the ceramic preform have a certain strength.
[0114] In a possible implementation, in S23, the drying temperature of the ceramic preform is 150-200° C., and the drying time is 20-40 min. The ceramic preform is placed in an oven or other device capable of heating and heat preservation for drying, and the drying temperature range is controlled to be 150-200° C., and the drying time is 20-40 min, to ensure that the moisture in the ceramic preform is completely removed.
[0115] In a possible implementation, in S23, the molten metal is high-chromium cast iron liquid or high-alloy steel liquid; and the temperature of the injected molten metal is controlled to be 1500-1580°C.
[0116] The temperature of the molten metal is controlled at 1500-1580℃, so that the molten metal maintains sufficient fluidity during the pouring process, fully penetrates into the gaps of the honeycomb ceramic preform, and completely fills the ceramic particles with molten metal. As the matrix material, high chromium cast iron and high alloy steel have high strength and hardness. After being compounded with ceramic particles, they can significantly improve the wear resistance, compressive strength and impact resistance of the composite material.
[0117] The present invention also provides a metal-based ceramic composite material, which is prepared by the metal-based ceramic composite material preparation method of the present invention. The metal-based ceramic composite material can be used to make roller sleeves, lining plates, and hammer heads.
[0118] In order to better understand the above-mentioned embodiments of the present invention, further description will be given below in conjunction with specific examples.
[0119] Example 1
[0120] This embodiment 1 provides a method for preparing a metal-based ceramic composite material, and the specific steps are as follows:
[0121] Step 1: Nanoscale processing of active substance powder
[0122] Step 11, mixing 500-mesh Al2O3 powder and 500-mesh B4C powder to obtain a mixed powder, wherein the weight ratio of the Al2O3 powder to the B4C powder is 1:1;
[0123] Step 12, 100 parts of the mixed powder in step 11 and 1 part of ammonium polyacrylate are put into a ball mill for ball milling. Zirconia balls are selected as grinding balls. The grinding balls have a diameter of 4 mm, a ball-to-material ratio of 3:1, and a ball mill speed of 100 r / min. Grind several times to prepare a preliminary active substance mixed powder;
[0124] Step 13, sieving the powder obtained in step 12 to remove the larger particles or ball milling media that are not ground finely, and separating the fine powder with a particle size of less than 90 nm;
[0125] Step 14, the fine powder separated in step 13 is put into the ball mill again for secondary ball milling, the grinding balls are zirconia balls, the grinding balls have a diameter of 3 mm, the ball-to-material ratio is 10:1, the ball mill speed is 150 r / min, and the ball milling time is 42 h;
[0126] Step 15: After the second ball milling, screening is performed again to finally obtain nano-scale active material powder with a particle size of less than 40 nm.
[0127] Step 2: Cold spraying of nano-scale active material powder on the surface of ceramic particles
[0128] Step 21, putting the zirconium corundum ceramic particles into a ball mill for ball milling at a speed of 50 rpm for 3 hours, then soaking them in acetone, ultrasonically cleaning them and drying them, and pickling the treated zirconium corundum ceramic particles to remove surface impurities and increase the surface roughness;
[0129] Step 22, placing the ceramic particles obtained after the treatment in step 21 in the spray chamber of the cold spray equipment, and preheating the ceramic particles, the preheating temperature is 700 ° C; the nano-scale active material powder finally obtained in step 1 is loaded into the powder feeder of the cold spray equipment, the gas source is compressed air, the gas source is turned on, the gas is heated by the gas spiral heater and then enters the nozzle, and merges with the nano-scale active material powder at the nozzle. The nano-scale active material powder is accelerated by the gas in the nozzle, sprayed out through the nozzle of the spray equipment, and hits the ceramic particles in the spray chamber to complete the deposition of the powder on the substrate;
[0130] The cold spraying parameters of the cold spraying equipment are as follows: the gas pressure is set to 1.5MPa, the compressed air is heated by a spiral heater, the heating temperature is 650°C, the powder delivery rate is 15g / min, the distance between the nozzle outlet and the sample spraying chamber is 20mm, ensuring that the deposition thickness of the nano-scale active substance powder on the surface of the ceramic particles is 30μm.
[0131] Step 3: Preparation of metal matrix ceramic composites
[0132] Step 31, 4 parts of sodium silicate aqueous solution are mixed with 1 part of water and then put into an atomizing device, the spray pattern is circular, the atomizing spray pressure is 0.2 MPa, the atomizing flow rate is 2 g / s, the atomizing time is controlled, and the mixed solution is evenly atomized on the surface of the ceramic particles with nano-scale active material powder deposited on the surface in step 2;
[0133] Step 32, filling the ceramic particles obtained in step 31 into a honeycomb mold, introducing CO2 gas for 1 minute, and then putting it into a drying room for curing at a drying room temperature of 100° C. for 18 hours to obtain a honeycomb ceramic preform;
[0134] Step 33, placing the ceramic preform obtained in step 32 into an oven for baking at a temperature of 150°C for 40 minutes to thoroughly dry out the moisture in the ceramic preform; fixing the dried honeycomb ceramic preform in a casting cavity, pouring a high chromium cast iron solution at a pouring temperature of 1580°C and a pouring speed of 8kg / s to obtain a metal-based ceramic composite material product.
[0135] Figure 1 The surface morphology of the metal-ceramic composite material prepared in this embodiment was observed under an optical microscope at 70 times. It can be seen that the ceramic particles are well combined with the metal matrix without defects. The composite area was observed under a scanning electron microscope. Figure 2 It can be clearly seen that there is a transition bonding layer (the dark part in the middle) between the ceramic particles and the metal matrix, indicating that after the surface is cold-sprayed with Al2O3 and B4C nano-mixed powder, the ceramic particles and the high-temperature molten metal achieve metallurgical bonding, further improving the bonding ability between the ceramic particles and the molten metal.
[0136] Example 2
[0137] This embodiment 2 provides a method for surface treatment of ceramic particles and preparation of metal-based ceramic composite materials, and the specific steps are as follows:
[0138] Step 1: Nanoscale processing of active substance powder
[0139] Step 11, mixing 600 mesh Al2O3 powder, 600 mesh SiC powder and 600 mesh B4C powder, wherein the weight ratio of Al2O3 powder, SiC powder and B4C powder is 1:1:2;
[0140] Step 12, 100 parts of the mixed powder in step 11 and 2 parts of sodium dodecyl sulfate are placed in a ball mill for ball milling. The grinding balls are silicon carbide balls with a grinding ball diameter of 5 mm, a ball-to-material ratio of 4:1, and a ball mill speed of 120 r / min to prepare a preliminary active substance mixed powder;
[0141] Step 13, sieving the nano-scale powder obtained in step 12 to remove the larger particles or ball milling media that are not ground finely, and separating the fine powder with a particle size of less than 70 nm;
[0142] Step 14, the fine powder separated in step 13 is put into the ball mill again for secondary ball milling, the grinding balls are silicon carbide balls, the grinding ball diameter is 4mm, the ball-to-material ratio is 8:1, the ball mill speed is 180r / min, and the ball milling time is 36h;
[0143] Step 15: After the second ball milling, screening is performed again to finally obtain nano-scale active material powder with a particle size of less than 30 nm.
[0144] Step 2: Cold spraying of active material powder on the surface of ceramic particles
[0145] Step 21, putting zirconium corundum ceramic particles and silicon nitride ceramic particles into a ball mill for ball milling, wherein the weight ratio of zirconium corundum to silicon nitride ceramic particles is 4:1, the ball mill speed is 60r / min, the ball milling time is 2h, and then soaking in acetone, ultrasonic cleaning and drying, and pickling the treated zirconium corundum ceramic particles to remove surface impurities and increase the surface roughness;
[0146] Step 22, placing the ceramic particles in step 21 in the spraying chamber of the cold spraying equipment, and preheating the ceramic particles, the preheating temperature is 600°C; loading the nano-scale mixed powder finally obtained in step 1 into the powder feeder of the cold spraying equipment, the gas source is argon gas, the gas source is turned on, the gas is heated by the gas spiral heater and enters the nozzle, and merges with the active material powder at the nozzle, the active material powder is accelerated by the gas in the nozzle, sprayed out through the nozzle of the spraying equipment, and hits the ceramic particles in the spraying chamber, completing the deposition of the powder on the substrate;
[0147] The cold spraying parameters of the cold spraying equipment are as follows: the gas pressure is set to 2MPa, the argon gas is heated by a spiral heater, the heating temperature is 700°C, the powder feeding flow rate is 20g / min, and the distance between the nozzle outlet and the sample spraying chamber is 15mm, ensuring that the deposition thickness of the nano-scale active material powder on the surface of the ceramic particles is 50μm.
[0148] Step 3: Preparation of metal matrix ceramic composites
[0149] Step 31, 5 parts of sodium silicate aqueous solution and 1 part of water are mixed and put into an atomizing device, the spray pattern is circular, the atomizing spray pressure is 0.4 MPa, the atomizing flow rate is 4 g / s, the atomizing time is controlled, and the mixed solution is evenly atomized on the surface of the ceramic particles with nano-scale active material powder deposited on the surface in step 2;
[0150] Step 32, filling the ceramic particles in step 31 into a honeycomb mold, introducing CO2 gas for 1 minute, and then putting it into a drying room for curing at a temperature of 90° C. for 22 hours to obtain a honeycomb ceramic preform;
[0151] Step 33, placing the ceramic preform obtained in step 32 into an oven for baking, the oven temperature is 180°C, the heating time is 30 minutes, and the moisture in the ceramic preform is completely dried; the dried honeycomb ceramic preform is fixed in the casting cavity, and a high chromium cast iron solution is poured at a pouring temperature of 1550°C and a pouring speed of 10kg / s to obtain a metal-based ceramic composite material product.
[0152] Example 3
[0153] This embodiment 3 provides a method for preparing a metal-based ceramic composite material, and the specific steps are as follows:
[0154] Step 1: Nanoscale processing of active substance powder
[0155] Step 11, mixing 700-mesh B4C powder, 700-mesh Al2O3 powder and 800-mesh iron-based self-fluxing alloy powder, wherein the weight ratio of the B4C powder, the Al2O3 powder and the iron-based self-fluxing alloy powder is 1:1:3;
[0156] Step 12, putting 100 parts of the mixed powder in step 11 and 3 parts of sodium dodecyl sulfate into a ball mill for ball milling, using stainless steel balls with a diameter of 6 mm, a ball-to-material ratio of 5:1, and a ball mill speed of 150 rpm to prepare a preliminary active substance mixed powder;
[0157] Step 13, sieving the powder obtained in step 12 to remove the larger particles or ball milling media that are not ground finely, and separating the fine powder with a particle size of less than 50 nm;
[0158] Step 14, the fine powder separated in step 13 is put into the ball mill again for secondary ball milling, the grinding balls are stainless steel balls, the grinding ball diameter is 5 mm, the ball-to-material ratio is 6:1, the ball mill speed is 200 r / min, and the ball milling time is 30 h;
[0159] Step 15: After the second ball milling, screening is performed again to finally obtain nano-scale active material powder with a particle size of less than 20 nm.
[0160] Step 2: Cold spraying of active material powder on the surface of ceramic particles
[0161] Step 21, putting zirconium corundum ceramic particles, silicon nitride ceramic particles and titanium carbide ceramic particles into a ball mill for ball milling, wherein the weight ratio of the zirconium corundum ceramic particles, the silicon nitride ceramic particles and the titanium carbide ceramic particles is 8:1:1, the ball mill speed is 80r / min, and the ball milling time is 1.5h, and then soaking in acetone, ultrasonic cleaning and drying, and pickling the treated zirconium corundum ceramic particles to remove surface impurities and increase the surface roughness;
[0162] Step 22, placing the ceramic particles treated in step 21 in the spray chamber of the cold spray equipment, and preheating the ceramic particles at a preheating temperature of 500° C. Loading the nano-scale mixed powder in step 1 into the powder feeder of the cold spray equipment, using argon as the gas source, connecting the gas source, and heating the gas through the gas spiral heater into the nozzle, where it merges with the active material powder, the active material powder is accelerated by the gas in the nozzle, sprayed out through the nozzle of the spray equipment, and impacting the ceramic particles in the spray chamber;
[0163] The cold spraying parameters of the cold spraying equipment are as follows: the gas pressure is set to 2.5MPa, the argon gas is heated by a spiral heater, the heating temperature is 800°C, the powder feeding flow rate is 25g / min, the nozzle outlet is 10mm away from the sample spraying chamber, the gas and the nano-scale mixed powder converge at the nozzle, the active material powder impacts the ceramic particles, and the powder is deposited on the substrate to ensure that the deposition thickness of the nano-scale mixed powder on the surface of the ceramic particles is 70μm.
[0164] Step 3: Preparation of metal matrix ceramic composites
[0165] Step 31, 7 parts of sodium silicate aqueous solution and 1 part of water are mixed and put into an atomizing device, the spray pattern is conical, the atomizing spray pressure is 0.6 MPa, the atomizing flow rate is 6 g / s, the atomizing time is controlled, and the mixed solution is evenly atomized on the surface of the ceramic particles with nano-scale active material powder deposited on the surface in step 2;
[0166] Step 32, filling the ceramic particles in step 31 into a honeycomb mold, introducing CO2 gas for 2 minutes, and then putting it into a drying room for curing at a temperature of 80° C. for 24 hours to obtain a honeycomb ceramic preform;
[0167] Step 33, placing the ceramic preform obtained in step 32 into an oven for baking at a temperature of 200°C for a heating time of 20 minutes to thoroughly dry out the moisture in the ceramic preform; fixing the dried honeycomb ceramic preform in a casting cavity, pouring a high chromium cast iron solution at a pouring temperature of 1530°C and a pouring speed of 12 kg / s to obtain a metal-based ceramic composite material product.
[0168] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0169] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for treating the surface of ceramic particles, characterized in that: include: S1, ball milling and cleaning the ceramic particles, removing impurities on the surface of the ceramic particles and increasing the surface roughness of the ceramic particles; S2. After preheating the pretreated ceramic particles, nanometer-scale active material powder is evenly deposited on the surface of the preheated ceramic particles by cold spraying to obtain treated ceramic particles.
2. A method for surface treatment of ceramic particles according to claim 1, characterized in that: The S1 includes: S11, ball milling the ceramic particles, and immersing the ball-milled ceramic particles in an acetone solution and cleaning them with ultrasonic vibration; S12, pickling the cleaned ceramic particles.
3. A method for surface treatment of ceramic particles according to claim 1, characterized in that: In S2, the preheating temperature is 300-700°C; During cold spraying, the gas pressure is controlled to be 1.5-5MPa and the inlet temperature of the accelerating gas is 100-800°C.
4. A ceramic particle surface treatment method according to claim 1, characterized in that: In S2, the steps for preparing nano-scale active material powder are as follows: S21, mixing different types of active substance powders according to proportion to obtain a first mixture; S22, adding the first mixture and the dispersant into a ball mill for ball milling, and sieving the second mixture of the first particle size from the ball-milled powder; S23, adding the second mixture and the dispersant into a ball mill and milling again to obtain a third mixture; and sieving out nano-scale active material powder of a second particle size from the third mixture.
5. A ceramic particle surface treatment method according to claim 1 or 4, characterized in that: In S21, the types of active materials include at least two of Al2O3 powder, B4C powder, SiC powder, Fe-based self-fluxing alloy powder and Ni-based self-fluxing alloy powder; The particle sizes of the Al2O3 powder, B4C powder and SiC powder are 500-700 meshes, and the particle sizes of the Fe-based self-fluxing alloy powder and the Ni-based self-fluxing alloy powder are 800-1000 meshes.
6. A ceramic particle surface treatment method according to claim 5, characterized in that: When the active substance includes two powders, the mixing ratio of the two powders is 1:1 to 1:2; When the active substance includes three powders, the mixing ratio of the three powders is 1:1:1 to 1:1:3; When the active material includes four or more powders, the four or more powders are mixed in equal proportions.
7. A method for treating the surface of ceramic particles according to claim 4, characterized in that: In S22, the diameter of the first grinding balls used in the ball mill is 4-6 mm, the first rotation speed of the ball mill is 100-150 r / min; the first ball-to-material ratio is 3:1-6:1; and the first particle size is less than 100 nm.
8. A method for treating the surface of ceramic particles according to claim 4, characterized in that: In S23, the diameter range of the second grinding balls used in the ball mill is 3-5 mm, the first rotation speed range of the ball mill is 150-220 r / min; the first ball-to-material ratio is 4:1-10:1; the second particle size is less than 50 nm; and the ball milling time range is 24-48 h.
9. A method for surface treatment of ceramic particles according to claim 7, characterized in that: The first grinding ball is any one of a silicon carbide ball, a zirconium oxide ball and a cemented carbide ball.
10. A ceramic particle surface treatment method according to claim 8, characterized in that: The second grinding ball is any one of a silicon carbide ball, a zirconium oxide ball and a cemented carbide ball.
11. A ceramic particle surface treatment method according to claim 4, characterized in that: The dispersant is ammonium polyacrylate and / or sodium dodecyl sulfate.
12. A method for treating the surface of ceramic particles according to claim 4, characterized in that: The ceramic particles in S1 are one or more of zirconium corundum ceramic particles, aluminum oxide ceramic particles, silicon nitride ceramic particles, titanium nitride ceramic particles, silicon carbide ceramic particles or titanium carbide ceramic particles.
13. A method for preparing a metal-based ceramic composite material, characterized in that: include: S1. Treating the surface of ceramic particles using the treatment method of claim 1 to obtain first ceramic particles; S2: Using the first ceramic particles to prepare a metal-based ceramic composite material S21, uniformly atomizing a mixture of a sodium silicate aqueous solution and water on the surface of the first ceramic particles to obtain second ceramic particles; S22, filling the second ceramic particles into a honeycomb mold, and obtaining a honeycomb ceramic preform after curing; S23, drying the ceramic preform, placing the dried ceramic preform in a mold cavity, injecting molten metal into the mold cavity and then solidifying the molten metal to obtain a metal-based ceramic composite material.
14. The method for preparing a metal-based ceramic composite material according to claim 13, characterized in that: In S21, the mixing weight ratio of the sodium silicate aqueous solution to water is 4:1 to 9:1; The atomization control atomization spray pressure is 0.2-0.8 MPa, the atomization flow rate is 2-10 g / s, and the atomization spray amount of the mixture of the sodium silicate aqueous solution and water accounts for 4%-8% of the total weight of the first ceramic particles; During the atomization process, the first ceramic particles are vibrated.
15. The method for preparing a metal-based ceramic composite material according to claim 13, characterized in that: The S22 includes: S221, filling the second ceramic particles into a honeycomb mold; S222, continuously introducing CO2 gas into the honeycomb mold for 1 to 2 minutes; S223, keeping the honeycomb mold at a temperature of 50 to 100° C. for 18 to 24 hours to solidify the second ceramic particles in the mold to obtain a honeycomb ceramic preform.
16. The method for preparing a metal-based ceramic composite material according to claim 13, characterized in that: In the step S23, the drying temperature of the ceramic preform is 150-200°C, and the drying time is 20-40 minutes.
17. The method for preparing a metal-based ceramic composite material according to claim 13, characterized in that: In S23, the molten metal is high-chromium cast iron or high-alloy steel; the temperature of the injected molten metal is controlled to be 1500-1580°C.
18. A metal-based ceramic composite material, characterized in that: The metal-based ceramic composite material is prepared by the preparation method of any one of claims 13 to 17.
Citation Information
Patent Citations
Composite reinforced wear-resistant part of metal-ceramic prefabricated member and manufacturing method of composite reinforced wear-resistant part
CN103143699A
Preparation method of extrusion roller
CN111283176A
Wear-resistant metal-ceramic composite material with long service life and preparation method thereof
CN112207273A
Composite preparation method for metal-based ceramic composite material
CN116441515A
Cited By
Preparation method of ceramic reinforced metal matrix composite material based on atomic layer deposition coating
CN121244909A